SPORT PSYCHOLOGY AND THE INFLUENCE ON ATHLETES’ EMOTIONS AND PERFORMANCE (Fiep Bulletin - online, 2025)
Introduction: Sports psychology is a crucial area for understanding how emotional and external factors influence athletes' performance. Knowing these aspects is essential to optimize performance and promote the well-being of athletes. Objective: This article aims to carry out a literature review on the relationship between Sports Psychology and emotional control and the performance of high-performance athletes. Methods: The research is a qualitative review of the literature carried out using the Google Scholar database. Review articles published between 2021 and 2023 in Portuguese that addressed the proposed themes were included. Results: The analysis revealed that emotional support, the management of mental fatigue and the presence of a supportive crowd positively impact athletes' performance. Family support and the management of psychological stress also play a crucial role, contributing to increasing athletes' motivation and self-confidence during competitions. Conclusion: Sports psychology is vital for maximizing athletes' performance, influencing motivation, stress management and emotional state. Recognizing and integrating psychological support is fundamental to improving sports performance and ensuring the well-being of athletes. It is recommended that sport psychology professionals be involved in supporting athletes to help manage emotional challenges and improve overall performance.
Keywords: psychology; emotions; athletes; physical performance; sports